Improving Processability and Efficiency of Resonant TADF Emitters: A Design Strategy. Issue 2 (3rd December 2019) - Hall, David; Suresh, Subeesh Madayanad; dos Santos, Paloma L.; Duda, Eimantas; Bagnich, Sergey; Pershin, Anton; Rajamalli, Pachaiyappan; Cordes, David B.; Slawin, Alexandra M. Z.; Beljonne, David; Köhler, Anna; Samuel, Ifor D. W.; et al.
Abstract: A new design strategy is introduced to address a persistent weakness with resonance thermally activated delayed fluorescence (R‐TADF) emitters to reduce aggregation‐caused quenching effects, which are identified as one of the key limiting factors. The emitter Mes3 DiKTa shows an improved photoluminescence quantum yield of 80% compared to 75% for the reference DiKTa in 3.5 wt% 1, 3‐bis( N ‐carbazolyl)benzene. Importantly, emission from aggregates, even at high doping concentrations, is eliminated and aggregation‐caused quenching is strongly curtailed. For both molecules, triplets are almost quantitatively upconverted into singlets in electroluminescence, despite a significant (≈0.21 eV) singlet‐triplet energy gap (Δ E ST ), in line with correlated quantum‐chemical calculations, and a slow reverse intersystem crossing. It is speculated that the lattice stiffness responsible for the narrow fluorescence and phosphorescence emission spectra also protects the triplets against nonradiative decay. An improved maximum external quantum efficiencies (EQEmax ) of 21.1% for Mes3 DIKTa compared to the parent DiKTa (14.7%) and, importantly, reduced efficiency roll‐off compared to literature resonance TADF organic light‐emitting diodes (OLEDs), shows the promise of this design strategy for future design of R‐TADF emitters for OLED applications. Abstract : A new multiresonance thermally activated delayed fluorescence (R‐TADF) emitter design is presented. Blue organic light‐emitting diodes (OLEDs) show high efficiency (maximum external quantum efficiency, EQEmax = 21.1%) and improved efficiency roll‐off compared to most reported R‐TADF OLEDs. Using high‐level quantum chemical calculations, it is demonstrated that small Δ E ST and large radiative rate arise from short‐range reorganization of the electron density.